If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 = 8(4y + 1) Reorder the terms: 24 = 8(1 + 4y) 24 = (1 * 8 + 4y * 8) 24 = (8 + 32y) Solving 24 = 8 + 32y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-32y' to each side of the equation. 24 + -32y = 8 + 32y + -32y Combine like terms: 32y + -32y = 0 24 + -32y = 8 + 0 24 + -32y = 8 Add '-24' to each side of the equation. 24 + -24 + -32y = 8 + -24 Combine like terms: 24 + -24 = 0 0 + -32y = 8 + -24 -32y = 8 + -24 Combine like terms: 8 + -24 = -16 -32y = -16 Divide each side by '-32'. y = 0.5 Simplifying y = 0.5
| 9/10-4/10 | | 12-.6x-.2x=-16 | | -8m+(-4)=-44 | | 7+6x=-33+2x | | 8y+y=45 | | 5*12x=6 | | -7(k+9)=9(k+5)-14k | | 2w+10w=48 | | -x-3=17+9x | | 7x-(4x-13)=40 | | 27/63 | | 3(2x-5)=44x-7 | | x+x+23+(x+23)/4=562 | | 4(4x-3)-6x=4(2x+3)-24 | | -20+2x=-12 | | -8x+9x=-1+7 | | -4(1+2r)-r=7(-r-4) | | 4(4x-3)-6x=4x+2(3x-6) | | x+25+4x=-34-4x-40 | | 6x+20+2x+4=90 | | 3x+3=4x+9 | | 6x+20+2x+4= | | 3(x-8)+x=4(x-7)+4 | | 25-(x+3)=2(2x+1) | | -5(m+1)-1=8m-7(7m+6) | | -150+5x=-4x+84 | | 2x-5=2x+6 | | 4x+10=6x-4 | | (8-10x*5x+4)=0 | | 5(6)+5(2)=5(6+2) | | 2(3x+1)=6x | | 21/48 |